2011
DOI: 10.4067/s0717-95022011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of the Humerus Segments in Indian Population

Abstract: SUMMARY:The aim of the present study was to obtain the measurements of the different humerus segments and to estimate the length of humeri from them. For this purpose 100 (51 left and 49 right) sex-aggregated, adult dry humerus from Indian population, were taken to analyze the morphometric details of the humerus segments. The distance between five different segments viz: most proximal point of the humeral head and greater tuberosity (HA), head of the humerus and surgical neck of humerus (HB), proximal and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 25 publications
(28 reference statements)
6
29
3
1
Order By: Relevance
“…These features can be frontal eminence, occipital bone, and other skull bones, features of the face, toot and mandible, the strength and massiveness of long bones, and the general structure of pelvic bone. Furthermore, it is also very important to obtain morphometric values by considering the size differences of various bones in male and female skeletons (Somesh et al;Desai & Shaik;Tellioglu & Karakas;Harun, 2008). In our study, morphometric features of humerus were identified in order to provide a reference study to other studies which aim to perform sex determination by using humerus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These features can be frontal eminence, occipital bone, and other skull bones, features of the face, toot and mandible, the strength and massiveness of long bones, and the general structure of pelvic bone. Furthermore, it is also very important to obtain morphometric values by considering the size differences of various bones in male and female skeletons (Somesh et al;Desai & Shaik;Tellioglu & Karakas;Harun, 2008). In our study, morphometric features of humerus were identified in order to provide a reference study to other studies which aim to perform sex determination by using humerus.…”
Section: Discussionmentioning
confidence: 99%
“…Right Left Akman et al (2006) 307.1±20.8 304.8±20.8 Bokariya et al (2011) 312.9±1.74 307.0±1.27 Niraj et al (2014) 308.5±19.16 307.2±16.13 Somesh et al (2011) 299.6±22.5 309.6±20.6 Desai & Shaik (2012) 292.3±22.9 289.45±21.8 Salles et al (2009) 313±23 305±16 Latimer & Lowrance (1965 303±17.71 300.85±18.35 Udhaya et al (2011) 302.8±24.4 299.9±20.1 Our study 304.1±17.3 300.4±23.9 Table IV. Maximum humeral lenght (mm).…”
Section: Researchersmentioning
confidence: 99%
See 1 more Smart Citation
“…Humerus is the longest bone of the upper limb and its morphometric measurements can be useful for descriptive and comparative purpose. Many studies have been conducted in India and abroad focussing on morphometric measurements of humerus [4,9,14,15,16]. .…”
Section: Length Of the Bonementioning
confidence: 99%
“…Selvakumar et al conducted a study to determine handedness from the morphometry of intertubercular sulcus of humerus [13]. Somesh and colleagues performed morphometric analysis of segments of humerus [14]. Lokanadham and colleagues conducted a morphometric analysis of dry humerus bones in Indian population and compared the parameters between both the sex [15].…”
Section: Introductionmentioning
confidence: 99%